Waste Land - Walker, Lucy (Almega Projects, 2010)
Coproduction: Brazil, UK. Filmed over nearly three years, the film follows successful art photographer Vik Muniz as he journeys from his home base in Brooklyn to the world's largest garbage dump on the outskirts of Rio de Janeiro in his native Brazil. There he photographs an eclectic band of “catadores”—self-designated pickers of recyclable materials. Muniz’s initial objective was to “paint” the catadores with garbage. However, his collaboration with these inspiring characters as they recreate photographic images of themselves out of garbage reveals both the dignity and despair of the catadores as they begin to re-imagine their lives. What begins as a search for artistic inspiration quickly develops into a deeper level of social engagement - for the artist, for the filmmaker, and for the audience. Muniz manages something that modern art rarely does: he changes their lives. Just as the garbage is transformed into art, these human rejects gain a new sense of self-worth.